An Empirical and Subjective Model of Upper Extremity Fatigue Under Hypogravity - Volkova, Tatiana; Nicollier, Claude; Gass, Volker (Frontiers in Physiology, 2022)
In the context of extra-terrestrial missions, the effects of hypogravity (0 < G < 1) on the human body can reduce the well-being of the crew, cause musculoskeletal problems and affect their ability to perform tasks, especially during long-term missions. To date, studies of the effects of hypogravity on human movement are limited to experiments on the lower limbs. Here, we extend the knowledge base to the upper limbs, by conducting experiments to evaluate the effect of hypogravity on upper limb physical fatigue and mental workload in participants. Our hypothesis was that hypogravity would both increase participant productivity, by reducing overall physical fatigue expressed in Endurance Time, and reduce mental workload. Task Intensity-Endurance time curves are developed especially in seated positions, while performing static, dynamic, repetitive tasks. This experiment involved 32 healthy participants without chronic problems of the musculoskeletal system aged 33.59 ± 8.16 years. Using the collected data, fatigue models were constructed for tasks of varying Intensity. In addition, all participants completed the NASA – Task Load Index subjective mental workload assessment, which revealed the level of subjective workload when executing different tasks. We found two trends in the empirical fatigue models associated with the difference between the strength capabilities of males and females. The first is a significant positive (p = 0.002) relation between Endurance time and gravity level (⅙ G Moon, ⅓ G Mars, 1G) with negative coefficient for males and females for a static task. And there is marginal relation (p < 0.1) between overall mental workload and gravity level with a positive coefficient for males and females for the same task. The same trend was observed for dynamic and repetitive tasks. We concluded that the Task Intensity-Endurance Time model, adapted to hypogravity in combination with subjective mental assessment, is useful to human fatigue investigation. The combination of these methods used for ergonomic analysis and digital human modeling, could improve worker productivity. Finally, this study may help prepare astronauts for long-term missions on the Moon and Mars and improve our understanding of how we can prevent musculoskeletal disorders caused by hazardous manual handling under such extreme environments.